Determination of motor vehicle taxpayer compliance: the role of tax socialization, tax sanctions, and tax amnesty programs with taxpayer awareness as a moderating variable (Case study of the Cibinong SAMSAT, Bogor Regency) - Roby Gusti Listianto; Listya Sugiyarti (Jurnal Mantik, 2026)
This study aims to examine the effect of tax socialization, tax sanctions, tax amnesty programs, and taxpayer awareness on motor vehicle taxpayer compliance at the Samsat Cibinong Bogor. The sampling method used was random sampling. The data used were primary data collected through questionnaires. 100 questionnaires were processed. And analyzed using SPSS version 30 with validity and reliability test methods, regression analysis, R2 test, f test, and t test. This study used multiple linear regression analysis to test the hypothesis. The results showed that tax socialization, tax sanctions, and tax amnesty programs at the Samsat Cibinong Bogor were categorized as good. The results of partial hypothesis testing proved that tax socialization, tax sanctions, and tax amnesty programs had an effect on motor vehicle taxpayer compliance. In moderation, taxpayer awareness could not mitigate the impact of tax socialization, tax sanctions, and tax amnesty programs on motor vehicle taxpayer compliance at the Samsat Cibinong Bogor